Evaluation of spatial distribution and regional zone delineation for micronutrients in a semiarid Deccan Plateau Region of India. (31st May 2018) - Shukla, Arvind Kumar; Sinha, Nishant Kumar; Tiwari, Pankaj Kumar; Prakash, Chandra; Behera, Sanjib Kumar; Surendra Babu, P.; Patnaik, M.C.; Somasundaram, J.; Singh, Pooja; Dwivedi, Brahma Swaroop; Datta, Siba Prasad; Meena, Mahesh C.; et al.
Abstract: Emerging micronutrient deficiencies in different soils of the world is a threat for sustainability of agriculture. As distribution of micronutrients in soil varies spatially, site‐specific management of micronutrients by delineating regional zones (RZs) is an effective strategy for precision agriculture. The current investigation was performed to delineate RZs in a Deccan Plateau Region (DPR) of India by considering spatial variability of some soil properties and available micronutrients for efficient management of micronutrients. Altogether, 4, 939 representative soil samples (with geographical coordinates) from surface (0–0.15 m depth) layers were obtained from Telangana state lying in DPR of India. After processing, soil samples were analysed for pH, electrical conductivity, soil organic carbon and available zinc, copper, iron, and manganese. Soil pH, electrical conductivity, and soil organic carbon content had mean values of 7.48 ± 0.95, 0.42 ± 0.22 dS/m and 0.48 ± 0.17%, respectively. Whereas, the mean values of available zinc, iron, copper, and manganese concentrations were 0.83 ± 0.36, 8.79 ± 4.15, 0.99 ± 0.43, and 8.79 ± 4.06 mg/kg, respectively. Geostatistical analysis divulged different distribution pattern of soil properties and available micronutrients with strong to moderate spatial dependency. The four principal components (with >1 eigenvalue) responsible for 73% of total variance were considered for analysis. Six RZs from the study area were created through geostatistical, principal component, and clustering analysis. The measured soil properties and available micronutrients in the RZs varied significantly highlighting the usefulness of RZ delineation technique for precise micronutrients management in DPR of India.